Izmenenie pokazatel'ei nasosnoi funktsii serdtsa y sportsmenov i nesportsmenov pri vypolnenii myshechnykh nagruzok povyshayushcheisya moshchnosti - Abzalov, R. A.; Nigmatullina, R. R. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The aim of this study was to analyze the pump function of a heart in athletes and non-athletes when performing the muscle loads of an increasing power. As the result of the research it had been concluded: the method of the impedance rheography allows to value the pump function of a heart - when working with the increasing power; indices of the pump functions of a heart change in dependence on the level of athletes sports trainingness, age and sex.